Melatonin from Plants: Going Beyond Traditional Central Nervous System Targeting—A Comprehensive Review of Its Unusual Health Benefits - Laurindo, Lucas Fornari; Simili, Otávio Augusto Garcia; Araújo, Adriano Cressoni; Guiguer, Elen Landgraf; Direito, Rosa; Valenti, Vitor Engrácia [UNESP]; de Oliveira, Vitor; de Oliveira, Juliana Santos; Yanaguizawa Junior, José Luiz; Dias, Jefferson Aparecido; Maria, Durvanei Augusto; Rici, Rose Eli Grassi; et al. (MDPI, 2025)
Melatonin is indispensable for the homeostasis of plants and animals. In humans, it can help prevent or be an adjuvant treatment for several diseases mainly related to the immune system, inflammation, and oxidative stress. Moreover, a melatonin-rich diet is linked to several health benefits, such as regulation of circadian rhythm, regulation of the immunological system, epilepsy control, delaying the aging process, and diminishing hormones related to cancer. This review aimed to show the effects of melatonin in diseases beyond its traditional use. The results showed it can present scavenging of free radicals, reducing inflammatory cytokines, and modulating the immune system. Moreover, it can improve insulin resistance, blood pressure, LDL-c, adipose tissue mass, adhesion molecules, endothelial impairment, and plaque formation. These effects result in neuro- and cardioprotection, improvement of liver diseases, rheumatoid arthritis, dermatitis, COVID-19, polycystic ovaries, and sepsis. We conclude that plant melatonin can benefit patients with many diseases besides sleep problems and neurodegeneration. Plant melatonin may be more cost-effective and present fewer adverse events than synthetic. However, more clinical trials should be performed to show adequate doses, formulation, and treatment time.
Keywords: cancer; cardiovascular diseases; COVID-19; dysbiosis; melatonin; plants; polycystic ovary syndrome; rheumatoid arthritis; sepsis